Cold‐inducible RNA‐binding protein promotes the development of liver cancer. Issue 4 (3rd March 2015) - Sakurai, Toshiharu; Yada, Norihisa; Watanabe, Tomohiro; Arizumi, Tadaaki; Hagiwara, Satoru; Ueshima, Kazuomi; Nishida, Naoshi; Fujita, Jun; Kudo, Masatoshi
Abstract : Most hepatocellular carcinomas (HCCs) develop in the context of chronic liver inflammation. Oxidative stress is thought to play a major role in the pathogenesis of HCC development. In this study, we examined whether cold‐inducible RNA‐binding protein (Cirp) controls reactive oxygen species (ROS) accumulation and development of HCC by using murine models of hepatocarcinogenesis and human liver samples. Cirp expression, ROS accumulation, and CD133 expression were increased in the liver of tumor‐harboring mice. Cirp deficiency reduced production of interleukin‐1β and interleukin‐6 in Kupffer cells, ROS accumulation, and CD133 expression, leading to attenuated hepatocarcinogenesis. Thioacetamide treatment enhanced hepatic expression of CD133 and phosphorylated signal transducer and activator of transcription 3 (STAT3), which was prevented by treatment with the antioxidant butylated hydroxyanisole. Intriguingly, the risk of human HCC recurrence is positively correlated with Cirp expression in liver. Cirp appears to play a critical carcinogenic function and its expression might be a useful biomarker for HCC risk prediction. Abstract : Cirp would enhance tumorigenesis by controlling ROS accumulation. Cirp might be associated with stem cell maintenance. Cirp expression might be a useful biomarker for HCC risk prediction.